On sequences of molecular descriptors related to some counting polynomials of a benzenoid graph - Nadeem, Muhammad,; Yousaf, Awais,; Razaq, Abdul, (Utilitas Mathematica, 2022)
Opposite edges in a connecting graph which lies in the same face eventually form a strip of adjacent faces and plays a major rule in the construction of counting polynomials. Polynomials are the sequel description of topological properties in such a way that the exponents represent the extent of its partitions while the coefficients are related to the occurrence of these partitions. Topological indices are used to model chemical properties of molecular graph. In this paper, we construct Omega, Sadhana, Theta and PI polynomials and, related sequences of degree based molecular descriptors of these polynomials. As a consequence of these generalized sequences; molecular descriptors for the graph T(0>pY) can be calculated without further calculation at any level. © 2020 Utilitas Mathematica Publishing Inc.. All rights reserved.